Balancing grit and ground: Cultural sustainability and resilience among marginalized scholars in academia - Aliari, Samira (Journal of International Students, 2025)
This study explores the interplay between grit and ground in the academic experiences of marginalized scholars, emphasizing the role of cultural sustainability in fostering resilience and success. The research highlights the structural barriers scholars face through qualitative narratives, including underrepresentation, institutional neglect, microaggressions, and cultural taxation. While grit enables scholars to navigate these challenges, the study argues that true academic inclusion requires systemic change that values cultural identity and community-based support. The findings suggest that cultural grounding strengthens individual resilience and enriches academic discourse by integrating diverse perspectives. Moreover, the study underscores the need for universities to move beyond symbolic diversity initiatives and implement policies that foster genuine inclusion, such as mentorship programs, equitable promotion criteria, and institutional recognition of diversity work. The research concludes that balancing grit with ground, individual effort with structural support, is essential for creating sustainable and equitable academic environments where marginalized scholars can thrive.